THE ʿILAL CONDITIONS OF AL-BAHR AL-KAMIL IN THE DIWAN OF ZUHAYR IBN ABI SULMA AS EDITED BY PROF. ʿALI HASAN FAʾUR - Syamsul Huda; Penny Respati Yurisa (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Poetry stands as one of the most elevated forms of Arabic literature and served as a central medium through which pre-Islamic Arabs documented events, values, and social realities. Its composition follows a strict metrical system built upon tafʿīlāt (metrical feet), which may undergo prosodic modifications known as ʿilal. These alterations provide poets with stylistic flexibility, allowing them to select words that reflect their emotional and social conditions while enhancing the expressive impact of their verses. The scholarly debate over the necessity of adhering to these ʿilal prompted the researcher to examine how pre-Islamic poets approached them, focusing particularly on Zuhayr ibn Abī Sulmā—one of the most esteemed figures in early Arabic poetry. His reputation for meticulous craftsmanship, polishing each poem over the span of a full year, earned his works the title ḥawliyyāt (“yearly refined poems”). This study aims to assess the extent to which Zuhayr adhered to prosodic ʿilal through a qualitative analysis based on library research. The findings indicate that Zuhayr consistently followed the prescribed ʿillah in the ḍarb (the final foot of the verse), demonstrating strict compliance with traditional metrical rules in this position. However, his adherence in the ʿarūḍ (the penultimate foot) was variable; in some instances, he maintained conformity with the expected form, while in others he opted for alternative structures to achieve stylistic or expressive aims. These observations suggest that Zuhayr’s poetic precision did not preclude artistic flexibility but rather reflected a balanced approach that honored classical prosody while accommodating creative expression.